The study protocol to evaluate implementation of the transitional care model in four U.S. healthcare systems during the Covid-19 pandemic. (May 2023) - Naylor, Mary D.; Hirschman, Karen B.; Morgan, Brianna; McHugh, Molly; Hanlon, Alexandra L.; Ahrens, Monica; McCauley, Kathleen; Shaid, Elizabeth C.; Pauly, Mark V.
Highlights: Study protocol of the implementation evaluation of the Transitional Care Model. Use of PRISM to guide study design and implementation. Qualitative and quantitative data collected independently then interpreted together. Parallel, convergent mixed methods used for ongoing assessment of implementation. Analyses planned to examine relationships between key variables and fidelity rates. Implications of study findings in the context of COVID-19 will be examined. Abstract: This study protocol describes the conceptual framework, design, and methods being employed to evaluate the implementation of the Transitional Care Model (TCM) as part of a randomized controlled trial. The trial, designed to examine the health and cost outcomes of at-risk hospitalized older adults, is being conducted in the context of the COVID-19 pandemic. This parallel study is guided by the Practical, Robust, Implementation and Sustainability Model (PRISM) and uses a fixed, mixed methods convergent parallel design to identify challenges encountered by participating hospitals and post-acute and community-based providers that impact the implementation of the TCM with fidelity, strategies implemented to address those challenges and the relationships between challenges, strategies, and rates of fidelity to TCM's core components over time. Prior to the study's launch and throughout its implementation, qualitative and quantitative data related to COVID and non-COVID challenges are being collected via surveys and meetings with healthcare system staff. Strategies implemented to address challenges and fidelity to TCM's core components are also being assessed. Analyses of quantitative (established metrics to evaluate TCM's core components) and qualitative data (barriers and facilitators to implementation) are being conducted independently. These datasets are then merged and interpreted together. General linear and mixed effects modeling using all merged data and patients' socio-demographic and social determinants of health characteristics, will be used to examine relationships between key variables and fidelity rates. Implications of study findings in the context of COVID-19 and future research opportunities are suggested. Trial registration: ClinicalTrials.gov Identifier: NCT04212962